Evidence for abasic site sugar phosphate-mediated cytotoxicity in alkylating agent treated Saccharomyces cerevisiae. - Michelle Heacock; Vladimir Poltoratsky; Rajendra Prasad; Samuel H Wilson (PLoS ONE)
To better understand alkylating agent-induced cytotoxicity and the base lesion DNA repair process in Saccharomyces cerevisiae, we replaced the RAD27(FEN1) open reading frame (ORF) with the ORF of the bifunctional human repair enzyme DNA polymerase (Pol) β. The aim was to probe the effect of removal of the incised abasic site 5'-sugar phosphate group (i.e., 5'-deoxyribose phosphate or 5'-dRP) in protection against methyl methanesulfonate (MMS)-induced cytotoxicity. In S. cerevisiae, Rad27(Fen1) was suggested to protect against MMS-induced cytotoxicity by excising multinucleotide flaps generated during repair. However, we proposed that the repair intermediate with a blocked 5'-end, i.e., 5'-dRP group, is the actual cytotoxic lesion. In providing a 5'-dRP group removal function mediated by dRP lyase activity of Pol β, the effects of the 5'-dRP group were separated from those of the multinucleotide flap itself. Human Pol β was expressed in S. cerevisiae, and this partially rescued the MMS hypersensitivity observed with rad27(fen1)-null cells. To explore this rescue effect, altered forms of Pol β with site-directed eliminations of either the 5'-dRP lyase or polymerase activity were expressed in rad27(fen1)-null cells. The 5'-dRP lyase, but not the polymerase activity, conferred the resistance to MMS. These results suggest that after MMS exposure, the 5'-dRP group in the repair intermediate is cytotoxic and that Rad27(Fen1) protection against MMS in wild-type cells is due to elimination of the 5'-dRP group.